Huamachuco along time: urban settlement and arquitecture - Cárdenas, Adriana Scaletti (2015)
Huamachuco is a city in the Highlands at the province of La Libertad (Peru), located in an inter-Andean valley at 3200 meters above sea level; it is surrounded by areas of great archaeological importance, such as Marcahuamachuco and Viracochapampa, and, quite recently, by mining activity areas. The city, where the last battle of the War of the Pacific occurred, is located 184 kilometers from Trujillo, on the northern coast of the country, but in every term, except the spatial one, it has remained relatively isolated from a number of national processes. The purpose of this article is to understand the settlement from the historical and architectural perspectives, aiming at the revalorization of the preserved material culture and at the characterization of the city as the holder of an interesting patrimonial collection.